Group-based psychoeducational workshop for parents in Kenya: findings from a pilot study - Alemu, Rediet Emebet Getnet; Nyatete, Hilda; Baseke, Rosine; Ngatia, Veronicah; Osborn, Tom L.; Wasanga, Christine M. (Frontiers in Public Health, 2023)
Introduction Low levels of mental health literacy amongst parents can have negative effects on youth mental wellbeing and help-seeking behaviors. Here, we explored the impact of a brief psychoeducational workshop on improving parent mental health literacy and family relationships in Kibera, a low-resource high-risk setting in Nairobi, Kenya. Methods The workshop was designed to address this issue, and it was delivered by trained facilitators to small groups of parents (N = 72). Data was collected at baseline, post-workshop, two-week follow-up, and one-month follow-up. Results Statistical and thematic analysis of the data revealed significant improvements in parent mental health literacy scores and family relationships, indicating the acceptability and effectiveness of this workshop. Discussion The findings suggest that brief, group-based psychoeducational workshops can be effective in improving parent mental health literacy and family relationships, thereby addressing challenges faced by parents and youth in the Kenyan context. Future studies are needed to conclusively determine if such workshops can improve participants’ own mental health or their perception of child behavior.